Academic Library Collections in the Age of Extended Reality (XR). Issue 2 (3rd July 2019) - Fujiuchi, Ken; Riggie, Joseph
Abstract: Extended Reality (XR) introduces a new way to preserve, record, and manage content. Collections traditionally focus on content in the form of books, documents, and multimedia. XR is a new form of media that can be difficult to integrate into current collections. In addition, through linked data, we can preserve the context that surrounds the content as well. Finally, XR media can incorporate digital manifestations of items from a library collection within its application. This technology review will explore the possibilities of XR in collection management, focusing on XR as a user interface, the impact on inventory management, and digital preservation.